A New View on Fuzzy F*-Structure Homotopy and its F*-Fundamental Group - V. Madhuri; B. Amudhambigai (Jordan Journal of Mathematics and Statistics, 2025)
In this paper, the concept of fuzzy F*-structure isomorphisms between F*-fundamental groups are studied. Also it is shown that, for every fuzzy F*-structure continuous function, there is an induced fuzzy F*-structure group homomorphism between their F*-undamental groups. Further in fuzzy F*-path connected space, all the F*-fundamental groups π1((X, J), xλ) are fuzzy F*-isomorphic. Also in fuzzy F*-path connected space, the F*-fundamental group π1((X; J), xλ) is independent of the fuzzy base point xλ up to fuzzy F*-structure isomorphism of groups. Key words and phrases. Fuzzy F*-structure isomorphisms, Fuzzy F*-structure homomorphisms, Fuzzy F*-structure loop homotopies, Induced fuzzy F*-structure group homomorphisms, Fuzzy F*-path connected spaces. 2000 Mathematics Subject Classification. 54A40, 54E55